PRODUCT DIFFERENTIATION AND BRAND AWARENESS STRATEGIES IN INCREASING INTEREST IN BECOMING SHARIA BANKING CUSTOMERS - Kartika, Neng Evi; Hardjadi, Dikdik; Gunawan, Wely Hadi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Islamic banking is a type of financial institution whose activities are based on sharia principles which aim to be free from usury. In the development of attracting people to become sharia banking customers, there are obstacles, especially in the marketing sector. So an appropriate marketing strategy is needed, so that sharia banking can be accepted by the public. In this research, as a form of sharia banking to win the competition, a product must be created that is different from similar products, this difference is called product differentiation. Apart from that, companies need to raise public awareness of their existence with a positive and innovative impression through the products they offer. This research uses descriptive quantitative research with a sample size of 100 people. The results of this research show that together product differentiation and brand awareness influence interest in becoming a customer; (2) product differentiation has a positive effect on purchasing interest; (3) brand awareness has a positive effect on purchasing interest.